Interpreting Psalm 22: Collective Suffering and National Hope in the Indonesian Context - Tanasyah, Yusak; Kurniawan, Mieke Cynthia; Hutapea, Jusuf (Indonesian Journal of Religious, 2025)
This article explores the significance of Psalm 22, particularly the poignant cry, "My God, my God, why have you forsaken me?" and its theological implications, both within the context of the psalm itself and its fulfillment in the crucifixion of Jesus Christ. By employing a theological-exegetical method, the study analyzes the psalm's literary structure and theological themes, particularly the expression of divine abandonment. The article then connects these themes to the Passion narratives in the New Testament, highlighting how Jesus' cry from the cross directly references and fulfills the prophetic words of Psalm 22. Furthermore, the paper incorporates insights from key theologians such as Bonhoeffer and Moltmann to explore the doctrine of a suffering God, emphasizing divine empathy in human suffering. The study extends to interfaith dialogue in Indonesia, examining how religious communities navigate social differences and contribute to fostering peace and tolerance through dialogue. By combining theological reflection with sociological analysis, the article underscores the importance of interfaith dialogue as a tool for promoting social cohesion and addressing religious intolerance. This paper contributes to both theological scholarship and interfaith studies by offering a comprehensive analysis of the intersection between suffering, redemption, and social harmony in the context of Psalm 22.